2020
DOI: 10.1002/ajs4.123
|View full text |Cite
|
Sign up to set email alerts
|

How many Australian veterans are homeless? Reporting prevalence findings and method from a national study

Abstract: This article presents findings from an Australian study of veteran homelessness (Hilferty, Katz et al. 2019). The AHURI Inquiry into Homelessness Amongst Australian Veterans was funded by the Department of Veterans' Affairs (DVA) to estimate the number of homeless veterans and to examine veterans' pathways into homelessness, service usage patterns and ways that service responses may be improved. This article presents the prevalence findings and describes the method employed by the research team. Drawing on pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Community Housing Industry Association (CHIA) is the national peak body representing registered not-for-profit social and affordable housing providers to policy and key decision makers in the Federal Government and its agencies. Motivated by Australian Housing and Urban Research Institute (AHURI) research commissioned by DVA 17 that found veterans were less likely to access mainstream services and reported high rates of dissatisfaction with services provided, CHIA together with RSL Care SA, have been collaborating to strengthen housing responses for homeless veterans. This research also identified that pathways to veteran homelessness, while similar to those of the general homeless population, also differ in that there can be a very rapid descent into homelessness for veterans once they separate from the ADF.…”
Section: What Has Been Done?mentioning
confidence: 99%
See 2 more Smart Citations
“…The Community Housing Industry Association (CHIA) is the national peak body representing registered not-for-profit social and affordable housing providers to policy and key decision makers in the Federal Government and its agencies. Motivated by Australian Housing and Urban Research Institute (AHURI) research commissioned by DVA 17 that found veterans were less likely to access mainstream services and reported high rates of dissatisfaction with services provided, CHIA together with RSL Care SA, have been collaborating to strengthen housing responses for homeless veterans. This research also identified that pathways to veteran homelessness, while similar to those of the general homeless population, also differ in that there can be a very rapid descent into homelessness for veterans once they separate from the ADF.…”
Section: What Has Been Done?mentioning
confidence: 99%
“…10 Moreover, the risk factors for veteran homelessness, such as the presence of mental disorders, including substance use disorders, overlap with those for suicide. 10,13,14 What has been done?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…• Provision of rental subsidies for young people and military veterans at risk of homelessness (Hilferty, Katz et al 2019), women who have experienced domestic and family violence, and other groups. Given the high demand and waiting lists for social housing, support for people in the private rental market is increasingly important to housing support.…”
Section: Introductionmentioning
confidence: 99%